Nouns with suffixes -ęt-/-ат-/-ят- in the ukrainian language (animate names) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Throughout all periods of the Ukrainian language, there have been many substantives, the formal structure of which includes suffix -ęt-. In Slavonic period, formant -ęt- was rather productive and served primarily as a suffix that created the denominations of young offspring. Diminutive, hypocoristic meaning is closely associated with it. In old-Russian-Ukrainian language, suffix -′aт- (nominative -′а), rarely -ат- (nominative –а) was involved mainly in the creation of the denominations of young animals. Further, this formant served as a means of derivation of children’s denominations. In the following periods of the Ukrainian language development the range of nouns with -ат-/-ят-, in addition to preserving old derivatives, grew as a result of individual author derivation.
Keywords: suffix; formant; neuter noun; animate names; nomina personalia